MRI of the upper airways in children and young adults: the MUSIC study. Issue 1 (29th October 2020) - Elders, Bernadette; Ciet, Pierluigi; Tiddens, Harm; van den Bosch, Wytse; Wielopolski, Piotr; Pullens, Bas
Abstract : Rationale: Paediatric laryngotracheal stenosis (LTS) is often successfully corrected with open airway surgery. However, respiratory and vocal sequelae frequently remain. Clinical care and surgical interventions could be improved with better understanding of these sequelae. Objective: The objective of this cross-sectional study was to develop an upper airway MRI protocol to obtain information on anatomical and functional sequelae post-LTS repair. Methods: Forty-eight patients (age 14.4 (range 7.5–30.7) years) and 11 healthy volunteers (15.9 (8.2–28.8) years) were included. Spirometry and static and dynamic upper airway MRI (3.0 T, 30 min protocol) were conducted. Analysis included assessment of postoperative anatomy and airway lumen measurements during static and dynamic (inspiration and phonation) acquisitions. Main results: Good image quality without artefacts was achieved for static and dynamic images in the majority of MRIs. MRI showed vocal cord thickening in 80.9% of patients and compared with volunteers, a significant decrease in vocal cord lumen area (22.0 (IQR 17.7–30.3) mm 2 vs 35.1 (21.2–54.7) mm 2, p=0.03) but not cricoid lumen area (62.3±27.0 mm 2 vs 66.2±34.8 mm 2, p=0.70). Furthermore, 53.2% of patients had an A-frame deformation at site of previous tracheal cannula, showing lumen collapse during inspiration. Dynamic imaging showed incomplete vocal cord abduction during inspiration in 42.6% and incomplete adduction during phonation in 61.7% of patients. Conclusions: Static and dynamic MRI is an excellent modality to non-invasively image anatomy, tissue characteristics and vocal cord dynamics of the upper airways. MRI-derived knowledge on postsurgical LTS sequelae might be used to improve surgery.